Knowledge, attitude and practice among mothers regarding common childhood illness - Gundluru, Muralidhar; Gopal, Harisha (International Journal of Contemporary Pediatrics, 2019)
Background: Since 1990 the global under-5 mortality rate has dropped from 91 deaths per 1000 live births in 1990 to 43 in 2015. But the rate of this reduction in under-5 mortality was insufficient to reach the MDG target of a two-thirds reduction of 1990 mortality levels by the year 2015. Leading causes of death in children under-5 years are preterm birth complications, pneumonia, birth asphyxia, diarrhoea and malaria. Methods: Present study is a cross sectional observational study conducted in the Department of Paediatrics, in JJM Medical College, Davanagere. Source of data was primary caregivers (mothers, fathers, grandparents, other relatives or guardians) of children between the age group of 1 month-5 years. This study is a structured questionnaire based cross-sectional observational study. Data collected was analysed using descriptive and inferential statistics. Results: Out of the 350 primary caregivers, 146(41.71%) were mothers, 97(27.71%) were fathers, 57(16.28%) were grandparents. Taboos and cultural beliefs to ward of illness were commonly practiced among this study group. 26% believed in skin branding their children during febrile episodes or convulsions. 8% believed that ear piercings would prevent diarrhoeal illnesses and infant deaths while 6% felt that amulets prevent respiratory illness and mortality. Overall knowledge among primary caregivers regarding common childhood illnesses was found to be good. Conclusions: Knowledge and attitude among primary caregivers regarding common childhood illnesses is favourable but the practices and perceptions are not satisfactory. Improving literacy rates will have a significant impact on reduction of childhood mortality. Socioeconomic development of the urban community can improve care seeking behaviour during the childhood illness.